Habituation to a predatory stimulus in a harvester (Arachnida, Opiliones) - Guilherme Ferreira Pagoti; Jerry A. Hogan; Rodrigo Hirata Willemart (Animal Cognition, 2024)
Abstract Several studies have investigated habituation in a defensive context, but few have addressed responses to dangerous stimuli. In such cases, animals should not habituate since this could cost their lives. Here we have stimulated individuals of the harvester Mischonyx squalidus with a predatory stimulus (squeezing with tweezers) in repeated trials within and between days, and measured the occurrence and magnitude of nipping, a defensive behavior. Contrary to our expectations, they did habituate to this stimulus. The probability and magnitude of response declined over trials during each of three days of testing in a typical habituation pattern. During the trials we also observed other defensive behaviors. We discuss our results mainly considering alternative defensive responses. Our data show that we lack information on (1) the role played by the ambiguity of stimuli, (2) the role played by subsequent stimuli and (3) the importance of the array of defensive behaviors of a species in understanding habituation. Although ubiquitous across animals and therefore expected, habituation is described for the first time in the order Opiliones.